Business Intelligence systems. New chances and possibilities for healthcare organizations - Olszak, Celina M.; Batko, Kornelia (Szanse i możliwości wykorzystania systemów Business Intelligence w organizacjach ochrony zdrowia, 2012)
The healthcare sector is one of the most developing sectors of the contemporary economy, increasingly considered in terms of market mechanisms. The managers of healthcare organizations need solutions that would allow them to improve decision-making, business processes, communication between doctors, patients and the administration, as well as effective access to different data. Business Intelligence systems may be helpful in this area. The article is only an outline of using BI for supporting the decision-making process in organizations in the healthcare sector. Our research attempts to answer the question concerning the general possibilities of using BI in healthcare organizations. Therefore, the main objective of our study is to identify the possibilities of using BI systems in healthcare organizations and the chances for healthcare organizations which appear due to BI systems implementation. The structure of the article is directed by this objective
Informatyka Ekonomiczna = Business Informatics, 2012, Nr 3 (25), s. 123-138
Keywords: Business Intelligence; healthcare organization; Hospital Information System; ochrona zdrowia; organizacje medyczne; szpitale; systemy informatyczne